Impact of CYP2B6 polymorphism on hepatic efavirenz metabolism in vitro. (June 2007) - Desta, Zeruesenay; Saussele, Tanja; Ward, Bryan; Blievernicht, Julia; Li, Lang; Klein, Kathrin; Flockhart, David A; Zanger, Ulrich M
Objectives: To determine the influence of cytochrome P450 2B6 ( CYP2B6 ) genotype on the rate of oxidative efavirenz metabolism in human liver microsomes.Materials  &  methods: Formation rates of 8-hydroxyefavirenz, 7-hydroxyefavirenz and 8, 14-dihydroxyefavirenz were determined in  vitro with efavirenz as a substrate (10  µµM) in a large panel of human liver microsomes (n  =  87) that were genotyped for variants of the CYP2B6 gene and phenotyped for CYP2B6 protein expression and bupropion hydroxylation.Results: Efavirenz 8-hydroxylation, the major route of efavirenz clearance, was detected in all samples, exhibiting an overall interindividual variability of 44.7-fold; 8, 14-dihydroxyefavirenz and 7-hydroxyefavirenz were also detected in most samples. The formation rate of 8-hydroxyefavirenz correlated significantly with CYP2B6 protein (Spearman''s rS   =  0.54; p  <  0.0001) and bupropion hydroxylase activity (rS     =  0.73; p  <  0.0001). Compared with the *1/*1 genotype, efavirenz 8-hydroxylation was significantly lower in samples with *1/*6 and *6/*6 genotype, which also had significantly decreased CYP2B6 protein (Mann––Whitney test, p  <  0.05). A decrease in CYP2B6 protein was also observed in samples with *1/*5 and *5/*6 genotypes, but this did not result in significant reduction of efavirenz metabolism, probably due to differences in specific activity of the protein variants. Lower CYP2B6 protein and activity, as well as efavirenz 8-hydroxylation was also found in several samples with rarer genotypes. We found no effect of gender and age on any of the phenotypes tested, but prior exposure to carbamazepine markedly increased CYP2B6 protein expression and activity as well as efavirenz 8-hydroxylation.Conclusions: We have shown that CYP2B6 genetic polymorphism markedly influences the metabolism of efavirenz in human liver microsomes. Importantly, the CYP2B6*6 allele harboring the SNPs c.516G>T [Q172H] and c.785A>G [K262R] was significantly associated with a pronounced decrease in CYP2B6 expression and activity, as well as a low rate of efavirenz 8-hydroxylation. These results represent a first step towards elucidating the mechanism by which this allele identifies patients exhibiting very high efavirenz plasma concentrations.